BP in Russia (B) - Bagley, Constance E.; Elias, Jaan ([London] : SAGE, 2016)
In his tenure at BP, Robert Dudley had developed a reputation for coolness under fire. Which was a good thing, since his assignments frequently put him in the cross hairs of powerful and angry interests. Dudley, the son of a U.S. naval officer, grew up on the Gulf Coast of the United States and then moved with his family to the Chicago suburbs for his high school years. He studied chemical engineering at the University of Illinois and earned an MBA at Southern Methodist University in Dallas. Then he went to work for AMOCO, the Chicago-based oil giant, and became known for developing fields and doing deals in Texas, Scotland, Russia and China. Case study (B) follows on from case study (A).
Originally Published in: Bagley, C.E., & Elias, J. (2012). BP in Russia (B). 12-013. New Haven, CT: Yale School of Management, Yale University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; British Petroleum Company; Strategic alliances (Business) -- Case studies; Crisis management -- Case studies; Petroleum industry and trade -- Russia (Federation) -- Case studies; Negotiation in business -- Case studies